Agricultural commodity price shocks and their effect on growth in sub-Saharan Africa - Tony Addison; Atanu Ghoshray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Commodity price shocks are an important type of external shock and are often cited as a problem for economic growth in sub-Saharan Africa. This paper quantifies the impact of agricultural commodity price shocks using a near vector autoregressive model. The novel aspect of this model is that we define an auxiliary variable that can potentially capture the definition of a price shock that allows us to determine whether the response of per capita Gross domestic product (GDP) growth in sub-Saharan Africa to these price shocks is asymmetric. We find that there is evidence of such asymmetric responses to commodity price shocks.
Keywords: E30; F40; O11; 330; commodity prices; external shocks; price shocks; economic growth; aid flows